Analysis of Environmental Work System Affecting Noise and Lighting at PT XYZ - Muhaemin, Yusup; Gumilar, Arcellia Citra Dewi; Doni, Rafi Safarian; Cepi; Henny, Henny (Universitas Komputer Indonesia, 2025)
Work system analysis at PT. XYZ was conducted to evaluate impact of noise and lighting on employee performance. Proper lighting supports clear vision and prevents accidents, while excessive noise can disrupt concentration, communication, and potentially cause hearing loss. This study aims to assess whether the levels of noise and lighting meet the government’s Threshold Limit Values (TLVs) and to provide recommendations for improving the work environment. Measurements were taken using a sound level meter and a lux meter, then analyzed using descriptive statistics. The results show that both noise and lighting significantly affect the comfort and performance of production operators. A suboptimal work environment can lead to fatigue and reduced work effectiveness. Therefore, improvements are recommended through proper noise and lighting adjustments or by using noise-reducing equipment such as soundproofing or personal protective equipment. These efforts are expected to enhance employee performance and ultimately boost overall company productivity.